1

The code is:

\documentclass{article}
\usepackage{graphicx} % Required for inserting images
\usepackage{wasysym, amsmath, amsfonts, amssymb, mathtools, mathrsfs, wasysym, cancel, extarrows, listings, fontspec}
\begin{document}
\begin{alignat*}{2}
    (4x^3y+2y^3x)dx&+(y^4-4x^4)dy=0 \big/ :xy \\
    4x^2+2y^2&+(\frac{y^3}x-4\frac{x^3}y)y'=0\big/ \smiley \\
    4x^2+2x^2z^2&+(x^2z^3-4\frac{x^2}{z})y'=0\big/ :x^2; x\ne 0\\
    4+2z^2&+(z^3-\frac 4z)(z'x+z)=0\Rightarrow 2z^3+4z+(z^4-4)(z'x+z)=0\\
    2z^3+(z^4-4)z'x&+z^5=0\Rightarrow \frac{\overbrace{z^4-4}^{(z^2-2)(z^2+2)}}{\underbrace{-2z^3-z^5}_{-z^3(z^2+2)}}dz=\frac {dx}x\\
    \int \frac{z^2-2}{-z^3}dz&=\int \frac{dx}x \Rightarrow -\ln|z|-\frac{1}{z^2}=\ln|x|+C\\
    &\boxed{-\ln|\frac yx|-\frac{x^2}{y^2}=\ln|x|+C}
\end{alignat*}
\end{document}

The output is: enter image description here


I want every line in the equation to be in the middle of the line. E.g. I wrote 31 characters in a line, so I want the 15th character to be in the middle of the line. The problem is that it takes time to "play" with the & so I thought maybe there is a way I could write it automatically in the middle.

2
  • 1
    Why do you need to use alignat? {gather} will centre your equations...
    – DrM
    Commented Jun 15 at 22:09
  • @DrM I know I wrote (using alignat*) in the title, but using gather is ok too.
    – A field
    Commented Jun 16 at 3:39

1 Answer 1

4

LIke this:

enter image description here

You should be aware that align, alignat align equations to inserted anchors &, meanwhile equations, gather equation only horisontal center in text area. So, in your MWE youi only need to remove all ampersands and replace alignat* with gather* as was sugested in @DrM comment and done in MWE below:

\documentclass{article}
\usepackage{fontspec}

\usepackage{graphicx} % Required for inserting images
\usepackage{amssymb, mathtools, wasysym,}
\begin{document}
\begin{gather*}
    (4x^3y+2y^3x)dx +(y^4-4x^4)dy=0 \big/ :xy \\
    4x^2+2y^2 +(\frac{y^3}x-4\frac{x^3}y)y'=0\big/ \smiley \\
    4x^2+2x^2z^2 +(x^2z^3-4\frac{x^2}{z})y'=0\big/ :x^2; x\ne 0\\
    4+2z^2 +(z^3-\frac 4z)(z'x+z)=0\Rightarrow 2z^3+4z+(z^4-4)(z'x+z)=0\\
    2z^3+(z^4-4)z'x +z^5=0\Rightarrow \frac{\overbrace{z^4-4}^{(z^2-2)(z^2+2)}}{\underbrace{-2z^3-z^5}_{-z^3(z^2+2)}}dz=\frac {dx}x\\
    \int \frac{z^2-2}{-z^3}dz =\int \frac{dx}x \Rightarrow -\ln|z|-\frac{1}{z^2}=\ln|x|+C\\
     \boxed{-\ln|\frac yx|-\frac{x^2}{y^2}=\ln|x|+C}
\end{gather*}
\end{document}
2
  • Thank you! For my information, is there a way to do it using alignat*?
    – A field
    Commented Jun 17 at 5:57
  • No, alignat will anchor equation at ampersand, but over their position you not have control. Their are placed so, that whole equation system is centered, as you got with your code.
    – Zarko
    Commented Jun 17 at 6:02

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .